Ethical and procedural concerns in Scopus’s decision to discontinue and delete indexed content: A case study of the international journal of innovative research and scientific studies - Jean, Natalie (International Journal of Innovative Research and Scientific Studies, 2025)
This editorial note presents a critical examination of Scopus’s 2025 decision to discontinue the indexing of the International Journal of Innovative Research and Scientific Studies (IJIRSS) and to retroactively delete its 2025 articles from the Scopus database. While Scopus holds an important position in ensuring the credibility and visibility of global research, the decision to remove already indexed articles raises serious ethical and procedural concerns. Drawing upon IJIRSS’s formal response to the Scopus Content Selection and Advisory Board (CSAB) and comparative evidence from other publishing cases, this commentary argues that the decision-making process behind such delisting lacks transparency, proportionality, and scholarly rigor. Furthermore, it contends that Scopus’s governance structure—wherein Elsevier retains overriding authority—undermines the independence and integrity of its evaluation process. The article calls for greater accountability and the establishment of an equitable, transparent framework for journal re-evaluation and content retention, emphasizing the need for Scopus to reaffirm its academic mission over commercial priorities.